Marijuana use, craving, and academic motivation and performance among college students: An in-the-moment study. (August 2015) - Phillips, Kristina T.; Phillips, Michael M.; Lalonde, Trent L.; Tormohlen, Kayla N.
Abstract: Introduction: Marijuana is the most commonly used illicit substance in the U.S., with high rates among young adults in the state of Colorado. Chronic, heavy marijuana use can impact cognitive functioning, which has the potential to influence academic performance of college students. It is possible that craving for marijuana may further contribute to diminished cognitive and affective functioning, thus leading to poor outcomes for students. Methods: College student marijuana users ( n  = 57) were recruited based on heavy use and completed ecological momentary assessment (EMA) via text-messaging. The association between marijuana use and craving in a college setting was explored, as well as how these variables might relate to academic motivation, effort and success. The participants were sent text messages for two weeks, three times per day at random times. Results: A temporal association between craving and marijuana use was found, where momentary craving positively predicted greater marijuana use. Similarly, as craving levels increased, the number of minutes spent studying decreased at the next assessment point. A negative association between momentary craving for marijuana and academic motivation was found in the same moment. Greater academic self-efficacy positively predicted cumulative GPA, while average minutes spent smoking marijuana was negatively related. Conclusions: Using EMA, marijuana craving and use were significantly related. These findings provide further evidence that heavy marijuana use is negatively associated with academic outcomes. Highlights: Craving predicted use in college students who frequently use marijuana. Craving was negatively associated with academic effort and motivation. Average minutes spent smoking marijuana was negatively related to GPA. Greater academic self-efficacy positively predicted GPA.